PHARMACOGNOSTIC STUDY OF BALIK ANGIN STEM BARK (Mallotus paniculatus (Lam.) Mull. Arg) - Fitriyanti; Nopita; Revita Saputri (Borneo Journal of Pharmascientech, 2019)
ABSTRACT Indonesia is rich with natural products that can be used as a medicine. One of the natural resources used traditionally in Borneo is Balik Angin stem bark as a medicine for diarrhea and swollen gums. In terms of its potential, it is necessary to research to provide a scientific basis for qualitatively describing pharmacognostic which includes organoleptic, macroscopic and microscopic and determining the identification of chemical compounds contained through reaction tests and thin layer chromatography profiles of ethanol extract 70%. The organoleptic test has the results in the form of a distinctive odor, brown color, and a feeling of tightness. In the macroscopic observation of the Stem bark has thick bark with a hard, coarse and cracked texture with a thin outer surface dark brown easy to peel and red gummy. Microscopic observations have identifiable fragments in the form of epidermal cells, cortex, and crystal oxalate. The identification of chemical compounds showed positive effects on tannins, saponins, flavonoids, triterpenoids, and quinones. Profile of TLC obtained 5 stains separated by eluent ethyl acetate: methanol: water with (7: 2: 1). Keywords : Mallotus paniculatus (Lam.) Mull. Arg, Pharmacognostic study, ethanol extract 70%.